Comparison of primary hepatic neuroendocrine tumors and non-hepatitis B non-hepatitis C hepatocellular carcinoma on contrast-enhanced ultrasound - Tan, Zhizhi; Li, Jiawu; Wu, Zhenru; Zhou, Zhengling; Yang, Lulu; Luo, Yan (Frontiers in Oncology, 2023)
Objective: The purpose of this study was to compare the sonographic features of primary hepatic neuroendocrine tumors (PHNETs) to those of non-hepatitis B and non-hepatitis C hepatocellular carcinoma (NBNC-HCC) on contrast-enhanced ultrasound (CEUS). Materials and Methods: Fourteen patients with a mean age of 56.9±12.2 (SD) years with histopathologically confirmed PHNET were included in the study. Twenty-eight patients with a mean age of 58.5±10.4 years with histopathologically confirmed NBNC-HCC were randomly selected as the control group. The clinical data, conventional ultrasound and CEUS features were retrospectively analyzed between PHNET and NBNC-HCC. Results: PHNET was more common in women (57.1%, 8/14 cases), and NBNC-HCC was more common in men (75.0%, 21/28) (P=0.040). No significant differences were observed in etiology, tumor marker, and liver function between the two group (P>0.05). Conventional ultrasound revealed that the tumor size of PHNET (10.1±4.7 cm) was larger than that of NBNC-HCC (5.9±3.8 cm) (P=0.006). NBNC-HCC was predominantly hypoechoic, while the echogenicity of PHNET varied (P=0.001). On CEUS, 57.1% (8/14) of PHNETs showed heterogeneous hyperenhancement, whereas 77.0% (21/28) of NBNC-HCC presented homogeneous hyperenhancement (P=0.015). Furthermore, 35.7% (5/14) of PHNETs showed early washout (onset of washout <60 s), which was significantly different from that of NBNC-HCC (3.7%, 1/28) (P=0.005). Conclusion: CEUS is helpful in discriminating between PHNET and NBNC-HCC. PHNETs mainly present as a single mass with a large size (>10 cm) in the liver. The CEUS showed that most PHNETs exhibited heterogeneous enhancement in the arterial phase, washout in the portal venous and late phases and early washout being more likely than NBNC-HCC. However, more imaging features need to be evaluated in a larger sample.